Relationship between childhood sexual abuse and attitudes toward premarital sexual permissiveness among middle school students in Luzhou, China - Zhang Rong; Zhang Wen; Liao Maoxu; Liu Ya; Fan Song; Wei Hui; Tan Xiaozhen; Ye Yunli (BMC, 2022)
Abstract Background In recent years, the number of adolescents engaging in premarital sex has increased, and an increasing number of childhood sexual abuse (CSA) cases have been reported in China. Many studies have indicated that CSA has a well-established association with risky sexual activities. However, only a limited number of studies have explored possible reasons for this association among middle school students, a population that may engage in premarital sex, which is critical for the development of interventions to prevent risky sexual behavior. Based on random samples of middle school students from a Chinese city, this article investigated the relationship between CSA and students' premarital sexual permissiveness (PSP). Methods In a cross-sectional study conducted between 2016 and 2017 in Luzhou, China, 2292 middle school and high school students aged 12-18 years were recruited by multistage random sampling. All students were administered anonymous questionnaires. Multiple linear regression and binary logistic regression analyses were conducted to analyze the relationship between CSA and PSP. Results The prevalence of CSA was 15.4% (354/2292; 95% CI: 14-16.9%). A higher percentage of male respondents (18.2%) than female respondents (12.9%) had experienced CSA. A positive association between CSA and PSP was found among students. Respondents who had suffered CSA exhibited greater PSP, and this relationship was observed in the male sample, female sample and the total student sample in Luzhou (β = − 3.76, P < 0.05; β = − 2.79, P < 0.05; and β = − 2.84, P < 0.05, respectively). Respondents who had suffered CSA were also more likely to express a double standard about premarital sex (odds ratio [OR] =1.41, P < 0.05), especially among male students (odds ratio [OR] =1.63, P < 0.05). Conclusions Sex differences in CSA and the relationship between CSA and PSP were significant among this large sample of middle school students in Luzhou (China). The findings suggest that experiencing CSA may be closely related to youth attitudes toward premarital sex, especially among males. Therefore, it is important to emphasize the prevention of CSA and provide adolescent reproductive health programs to reduce the impact of CSA on sexual cognition and attitude, prevent premarital sex and promote positive attitudes toward sexual equality for middle school students.